Psychological rehabilitation of individuals with alcohol use disorder, drug addiction, gambling disorder, and codependency - Aidos Ibragim; Bakytgul Issatayeva; Kundyz Kuanzhanova; Almagul Mandykayeva; Aliya Mambetalina (Acta Psychologica)
The objective of this study was to assess the impact of a 12-month course of cognitive behavioral therapy (CBT) on individuals diagnosed with alcohol use disorder, drug addiction, gambling disorder, and codependency, with a focus on improving quality of life and reducing symptom severity. A quantitative design was employed, involving both control and experimental groups, each initially comprising 100 participants. By the end of the study, the final sample sizes in the experimental groups were 72 (alcohol use disorder), 70 (drug addiction), 74 (gambling disorder), and 73 (codependent behavior) individuals. An equal number of participants in the corresponding control groups were reassessed. Quality of life was measured using the World Health Organization Quality of Life BREF instrument, which measures physical health, psychological health, social relationships, and environmental conditions. The results indicated a significant improvement in quality-of-life scores in the experimental groups compared to the control groups. The Wilcoxon signed-rank test confirmed statistically significant improvements (p < 0.001) across all addiction categories, while the Mann-Whitney U test demonstrated substantial post-intervention differences between control and experimental groups (p < 0.001). Participants in the experimental group showed marked reductions in addiction severity, as indicated by AUDIT, DAST, G-SAS, and Spann-Fisher Codependency Scale assessments. Effect sizes (Cohen's d) ranged from 2.83 to 3.47, confirming the strong impact of psychotherapy. These findings underscore the effectiveness of CBT in reducing addiction severity and enhancing quality of life, supporting its broader integration into addiction treatment programs. The study provides valuable evidence for addiction rehabilitation efforts in Kazakhstan. From a practical perspective, these findings highlight the importance of structured psychotherapeutic interventions in addressing addiction-related issues. The study underscores the need to expand access to CBT in rehabilitation centers, particularly in regions with high addiction rates. Future policy initiatives should prioritize the development of therapist training programs and the implementation of evidence-based treatment methods. Moreover, the results emphasize the necessity for continuous post-treatment support to maintain long-term recovery and prevent relapse. By incorporating CBT into standardized rehabilitation protocols, policymakers and healthcare providers can enhance the overall effectiveness of addiction treatment services.